Atividade de estudo como fundamento do desenvolvimento do pensamento teórico de crianças em idade escolar inicial - Clarindo, Cleber Barbosa da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Dissertation presented to the Program of Postgraduate Education Program in the Faculty of Philosophy and Sciences, Universidade Estadual Paulista - UNESP - Marília, aims to understand and show how learning activity, through its content, the theoretical knowledge, enables the major changes in the way the school children understand and analyze the world of phenomena, relations and human assets. This formulation is due to the realization that learning activity, understood by theorists of Cultural-Historical Theory as the main activity of the school children, has a great importance in the formation of intellectual and cognitive strengths of these children in the early years of elementary school, because it develops in them a theoretical relationship toward the world. By means of the theoretical knowledge new capabilities are developed in the subjects, that enable them develop of a new form of action to realize their relation with the human world. Such understanding contrasts with the reality of our public schools which, as a rule, have failed to develop these skills in students. We hypothesized that the learning activity is a suitable option for the development of pedagogical work that aims to develop in the students higher psychological new formations that allow the appropriation of the most elaborate contents existing in human culture and, with it, a new way to think and act in the environment where they live. This study is characterized as a theoretical one; for its development actions were realized to locate, gather and analyze theories contained in publications, texts, articles and books by authors from Cultural-Historical Theory that discuss the issues focused on learning activity, theoretical thinking and the role of the teaching process in children development. In this context our research has as its main result the finding that school children have historically cognitive reserves to appropriate forms of theoretical...

Dissertação apresentada ao Programa de Pós-graduação em Educação da Faculdade de Filosofia e Ciências, Universidade Estadual Paulista - UNESP - Campus de Marília e vinculada à Linha de Pesquisa Teoria e Práticas Pedagógicas, tem como objetivo geral compreender e evidenciar como a atividade de estudo, por meio de seu conteúdo - o conhecimento teórico - possibilita as grandes transformações no modo pelo qual as crianças em idade escolar compreendem e analisam o mundo dos fenômenos, das relações e dos bens culturais humanos. Tal formulação é decorrente da compreensão de que, a atividade de estudo, entendida pelos teóricos da Teoria Histórico-Cultural como a atividade principal de crianças em idade escolar, tem grande importância na formação das forças intelectuais e cognitivas dessas crianças, principalmente nos anos iniciais do ensino fundamental, porque desenvolve nelas uma relação teórica com o mundo. Por meio do conhecimento teórico desenvolvem-se, no escolar, novas capacidades que lhe possibilitam o desenvolvimento de uma nova forma de ação para concretizar sua relação com o mundo humano. Tal compreensão contrasta com a realidade de nossas escolas públicas as quais, via de regra, não têm conseguido desenvolver nos estudantes essas capacidades. Partimos da hipótese de que a atividade de estudo é uma opção adequada para o desenvolvimento do trabalho pedagógico que objetiva desenvolver nos estudantes novas formações psicológicas superiores que possibilitem a apropriação do que há de mais elaborado na cultura humana e, com isso, um novo modo de pensar e agir no meio em que vivem. Caracteriza-se como um estudo teórico para o desenvolvimento do qual foram realizadas as ações de localizar, reunir e analisar teorizações contidas em publicações, textos, artigos e livros de autores da Teoria Histórico-Cultural que discutem as questões centradas na atividade de estudo, pensamento teórico...
Keywords: Educação de crianças; Ensino fundamental - Estudo e ensino; Metodos de ensino; Aprendizagem; Teaching methods